Lessons Learned Using Logic Models to Design and Guide DNP Projects. Issue 5 (14th September 2021) - Idzik, Shannon; Buckley, Kathleen; Bindon, Susan; Gorschboth, Susan; Hammersla, Margaret; Windemuth, Brenda; Bingham, Debra
Abstract : Supplemental digital content is available in the text. Abstract : Background: A final culminating project that is derived from a practice immersion experience is a critical part of a doctor of nursing practice (DNP) program. Problem: Many schools use well-designed quality improvement (QI) projects to meet this requirement, but there is no consensus on which QI methods and tools are the most effective for DNP students to demonstrate before graduation. Approach: One Mid-Atlantic public university began using QI process models, one of which was a logic model, to guide their DNP projects. This led to subsequent changes in the curriculum, faculty preparation, and practice partner responsibilities. Outcome: Many benefits and challenges were identified during the logic model implementation that may benefit other schools seeking to increase consistency and rigor. Although the learning process for students and faculty may be challenging, the outcomes included improved project conceptualization, clarity, concision, and feasibility of goal attainment. Conclusions: Use of logic models expands DNP students' skills to develop and implement a successful project and supports clinical scholarship.